(untitled) (UNED Research Journal, 2020)
Introduction: The Conservation Action Plan of the Orinoco crocodile (Crocodylus intermedius) includes in its activities the release of captive-bred specimens back into the wild. By monitoring these specimens in their natural habitat their adaptability is assessed. However, an accurate identification system is necessary to recognize the individuals when they are recaptured. Objetive: Determinate if Swanepoel or Boucher et al. for crocodile identification for the Orinoco crocodile is useful. Methods: A total of 543 Orinoco crocodiles were photographed and each photo was vectorized by drawing dark spots greater than 25% for each scute, in the first 10 lines of double caudal scales of the tail on the right side. Two system codes were evaluated, one is a numeric code described by Swanepoel and the other is an additive code described by Boucher et al. Results: A total of 464 Swanepoel codes and 537 Boucher et al. codes based on the dark spot pattern of the scales on the right side of the tails were generated for the 543 specimens. Both methods yielded high code values, however, the one developed by Boucher et al., with a 98.90% differentiation of the analyzed specimens, worked better. Conclusion: The study confirms that using the method of spots in the tail of crocodiles is an effective tool for identifying individual crocodiles.